DEEP LEARNING FOR ESTIMATION SYSTEM OF MULTIPHASE FLOWRATES OF OIL AND GAS PRODUCTION WELLS - Nurmalia, Enung
Artificial intelligence, evolving within the models of deep learning and machine learning, has shown widespread applications in various fields. One of the industries that has increasingly embraced the potential of artificial intelligence is the oil and gas sector.